Evaluation of osayidelera, a campaign addressing risk perceptions of COVID-19 in Blantyre, Malawi - Maganga, Chiyembekezo Focus (My University, 2024)
Background- Osayidelera COVID-19 was a national campaign that was implemented as part of Malawi’s Risk Communication and Community Engagement response for the pandemic. The campaign was designed to address low COVID-19 risk perceptions and enhance compliance to preventive behaviours. Despite massive resources that were channeled towards the campaign, there were no studies that had evaluated the effectiveness of Osayidelera in addressing low risk perception in Malawi, and that had measured the association between the risk perceptions and preventive behaviours in Malawi. This study set out to change that, by testing associations between exposure to the campaign and both risk perceptions and protective behaviours in the context of Blantyre, one of areas hardest hit by COVID-19 in Malawi. Methods- A cross-sectional survey was conducted in Blantyre from 6 to 20 May, 2022. A sample of 224 adults (18 and older) were drawn from rural, peri-urban and urban locations in Blantyre using a multi-stage sampling technique. Data were cleaned in Microsoft Excel and analysed in STATA. Descriptive statistics were used to characterise the study sample, campaign exposure, risk perceptions and behaviours. Logistic regression models were used to test associations between campaign exposure and risk perceptions, and risk perceptions and protective behaviours. Results- Overall, 63% of the sample reported low COVID-19 risk perceptions. The only sociodemographic variables associated with low risk perception in the multivariate logistic vi model were those who were divorced (aOR=0.20, p=0.046 CI=0.04-0.97) and widowed (aOR=0.10, p=0.009 CI=0.02-0.57); they had significantly lower odds of low risk perceptions than those who were single. Exposure to COVID-19 campaign was generally low, with only 27% of the respondents reporting high levels of exposure. The proportion of respondents who could recall exposure to the name “Osayidelera” was even lower, at 16%. In the multivariate logistic model, males had higher odds of high exposure to the campaign as compared to females (aOR=3.75, p=0.001 CI=1.66-7.69) with those odds even higher among respondents in periurban areas versus rural areas (aOR=6.15, p=0.043 CI=1.06-35.71). High COVID-19 knowledge was also significantly associated with exposure to the COVID-19 campaign (aOR=2.48, p=0.013 CI=1.21 - 5.06). The results showed no significant association between campaign exposure and risk perceptions (p>0.05). In the adjusted multivariate logistic regression model, only those living in Blantyre urban had significantly higher odds of low risk perceptions as compared to those living in Blantyre rural (aOR=4.83, p=<0.001, CI= 2.15- 10.85) All other factors were non-significant. Finally, we found that adherence to preventive behaviours was generally poor, with only 29% reporting high levels of adherence, regardless of their COVID-19 risk perceptions. Risk perceptions were not associated with preventive behaviours. Conclusion- This study established that there was low reach of the campaign in Blantyre, and that the relationship between risk perceptions and adoption of preventive behaviours was not as strong and positive as hypothesized by the campaign. Campaign designers may need to revisit assumptions about their theory of change. The study contributes to growth of scholarship on health promotion campaigns and risk communication by showing factors associated with the reach of the campaign and with risk perceptions
A research report submitted in partial fulfilment of the requirement for the degree of Masters of Public Health to the Faculty of Health Sciences, University of the Witwatersrand, School of Public Health, Johannesburg, 2023